Toward a better understanding of the impact of bioenergy use on mortality rate in EU28 region - Mohd Alsaleh; Zubair, Azeem Oluwaseyi; Abdul Rahim, Abdul Samad (Springer, 2021)
The objective of this research is to examine the impact of bioenergy usage on health outcomes, especially adult mortality in both developed and underdeveloped countries in the European Union, where the use of solid biomass is growing to generate bioheat, biocool, and biopower. Over the period studied, findings indicate that increased consumption of bioenergy has increased mortality rates in developed and underdeveloped EU28 countries during the period 1990–2018. This feedback proposes, using generalized least squares (GLS), that the resulting death rate from burning biomass-related cases is higher in the EU15 developed countries compared to EU13 underdeveloped countries. There is a need to lower burning biomass in the entire EU15 countries, more importantly its developed region, by critically evaluating the bioenergy production life cycle before it is available for final consumption. However, there is a continuous need to intensify stringent production procedures in the bioenergy industry in EU15 countries, more importantly the imported biomass crops for energy use. There is also a need to be consistent with the campaign on the usage of bioenergy products, i.e., bioheat, bioelectricity, and biofuels, particularly in the rural areas where the use of wood fuels for cooking, heating, and cooling are significant in EU15 developed countries in comparison to EU13 developing countries.